The Influences of Tutorial Discussion on Achievement of The Learning Objectives Immunology Block at Faculty of Medicine Sebelas Maret University - Al-Hazmy, Abdullah; Kusumawati, Ratna; Aryoseto, Lukman (Nexus Pendidikan Kedokteran dan Kesehatan, 2015)
Background: Tutorial discussion is one method of Problem Based Learning (PBL), this method divided students into small groups and then given a mdical case as a trigger to search further information, and they discuss knowledge and information that accompanied by a tutor. The success of the tutorial discussion process may affect the achievement of learning objectives block. The aim of the research is to determine differences in the achievement of learning objectives Immunology block scenarios before and after tutorial discussion. Methods: This research was a longitudinal observational analytic. The data were collected by using simple random sampling with 47 sampels of students batch 2013 and had been assessed at Medical Faculty of Sebelas Maret University. The learning objectives of this comparation study measured by pretest and posttest questions that have been tested validation by experts. The study was conducted using quantitative method and the results were analyzed by using Paired t-test. Results: The average value of pretest-posttest before and after tutorial discussion is 28.51-60.85 for the first scenario, 22.34-62.55 for the second scenario, and 16.81-65.32 for the third scenario. Paired t-test results showed significant differences with p <0.05 (p=0.000) Â for the value of pretest-posttest three scenarios. Conclusions: The achievement of learning objectives scenario in immunology block before and after tutorial discussion is significant. Keywords: tutorial discussion, learning objectives, Immunology block Â